Short-Term Observation of Ultrasonic Cyclocoagulation in Chinese Patients with End-Stage Refractory Glaucoma: A Retrospective Study - Dongpeng Hu; Shu Tu; Chengguo Zuo; Jian Ge (Journal of Ophthalmology)
Purpose. To assess the efficacy and safety of HIFU-based ultrasonic cyclocoagulation in Chinese patients with end-stage refractory glaucoma. Method. Patients were recruited consecutively from May 2016 to May 2017 in the Zhongshan Ophthalmic Center. Ultrasonic cyclocoagulation was performed on every patient, using the EyeOP1 ultrasound emitting device. Return visits were set at 1 day, 7 days, 1 month, and 3 months after the treatment. An intraocular pressure (IOP) reduction of ≥20% while IOP ≥ 5 mmHg was deemed as success. Mean IOP change was assessed. Efficacy of two modes (6 sectors and 8 sectors) was also compared. Complications were recorded for safety evaluation. Results. 61 eyes were treated in this study. The baseline IOP (mean ± SD) was 41.11 ± 10.65 mmHg. The percentage of IOP reduction after treatment was 29.2%, 43.2%, 34.8%, and 23.1% at 1 day, 7 days, 1 month, and 3 months, respectively. Overall success rate at 3 months was 50.0% (26/52). No significant difference was found between the 6 sectors group and the 8 sectors group in terms of the success rate (48.6% vs. 52.9%, p=0.768) as well as IOP reduction (p=0.417) at 3 months. Primary angle-closure glaucoma (PACG) had the highest success rate (80.0%, 12/15). Scleral thinning existed in 12 eyes, among which 2 developed hypotony (2 mmHg and 3 mmHg). Average pain score decreased massively compared with baseline data. Conclusion. With high percentage of IOP reduction and a good safety profile observed in our study, HIFU-based ultrasonic cyclocoagulation might become a promising alternative to cyclodestructive methods. Long-term efficacy and safety need further assessment. The study was registered with Chinese Clinical Trial Registry (http://www.chictr.org.cn; Registration number: ChiCTR-OOC-17014028).